Cerebral Sinus Venous Thrombosis and Prothrombotic Risk Factors in Children: A Single-Center Experience From Turkey. Issue 6 (August 2018) - Ozcan, Alper; Canpolat, Mehmet; Doganay, Selim; Unal, Ekrem; Karakukcu, Musa; Ozdemir, Mehmet A.; Patiroglu, Turkan
Abstract : Background: Cerebral sinus venous thrombosis (CSVT) is a rare cerebrovascular disease that may be life-threatening, especially in children. Objective: The purpose of this study was to assess the clinical presentation, radiologic imaging, underlying conditions, treatment, and outcomes of children with CSVT. Patients and Methods: In total, 23 consecutive children aged between 1 month to 18 years with CSVT, who were followed-up in Erciyes University Children's Hospital, were retrospectively enrolled in the study from January 2000 to December 2016. Results: The median age of the 23 children (13 female patients, 10 male patients) at initial diagnosis was 60 months (1 to 204 mo). The most common clinical manifestation was headache/irritability (n=9). The most common site of the CSVT was the transverse sinus (n=16). The most common prothrombotic risk factor was protein C deficiency (n=4). Underlying risk factors were detected in 15 patients. Genetic risk factors such as protein C deficiency, infections, trauma, malignancies, autoimmune hemolytic anemia, neurometabolic disorders, asphyxia, and cardiac malformations were common risk factors. Six children died. Multiple sinus involvement and parenchymal hemorrhages were seen in 4 and in 3 of the 6 children who died, respectively. Conclusions: Protein C deficiency seemed to be relatively high in the presented children. Multiple sinus involvement and additional parenchymal hemorrhages represent poor prognostic features.